BY THE NUMBERS: MAKASSAR’S TRADE, CENTRALIZED STATISTICS AND LOCAL REALITIES - Sutherland, Heather (Masyarakat Indonesia, 2013)
The valuable trade statistics provided by the Netherlands Indies government are a boon to researchers, but should not be accepted at face value. The extent to which shippers avoided registration is indicated by a comparison of Makassar’s trade figures before and after it was made a free-port in 1847, while early twentieth-century data from Makassar itself show a significantly higher level of maritime traffic than Batavia’s do. This suggests that central statistical series can seriously misrepresent local trade.